International Olympic Committee (IOC) consensus statement on acute respiratory illness in athletes part 2: non-infective acute respiratory illness. Issue 19 (27th May 2022) - Schwellnus, Martin; Adami, Paolo Emilio; Bougault, Valerie; Budgett, Richard; Clemm, Hege Havstad; Derman, Wayne; Erdener, Uğur; Fitch, Ken; Hull, James H; McIntosh, Cameron; Meyer, Tim; Pedersen, Lars; et al.
Abstract : Acute respiratory illness (ARill) is common and threatens the health of athletes. ARill in athletes forms a significant component of the work of Sport and Exercise Medicine (SEM) clinicians. The aim of this consensus is to provide the SEM clinician with an overview and practical clinical approach to non-infective ARill in athletes. The International Olympic Committee (IOC) Medical and Scientific Committee appointed an international consensus group to review ARill in athletes. Key areas of ARill in athletes were originally identified and six subgroups of the IOC Consensus group established to review the following aspects: (1) epidemiology/risk factors for ARill, (2) infective ARill, (3) non-infective ARill, (4) acute asthma/exercise-induced bronchoconstriction and related conditions, (5) effects of ARill on exercise/sports performance, medical complications/return-to-sport (RTS) and (6) acute nasal/laryngeal obstruction presenting as ARill. Following several reviews conducted by subgroups, the sections of the consensus documents were allocated to 'core' members for drafting and internal review. An advanced draft of the consensus document was discussed during a meeting of the main consensus core group, and final edits were completed prior to submission of the manuscript. This document (part 2) of this consensus focuses on respiratory conditions causing non-infective ARill in athletes. These include non-inflammatory obstructive nasal, laryngeal, tracheal or bronchial conditions or non-infective inflammatory conditions of the respiratory epithelium that affect the upper and/or lower airways, frequently as a continuum. The following aspects of more common as well as lesser-known non-infective ARill in athletes are reviewed: epidemiology, risk factors, pathology/pathophysiology, clinical presentation and diagnosis, management, prevention, medical considerations and risks of illness during exercise, effects of illness on exercise/sports performance and RTS guidelines.